Comparative assessment of gingival thickness in pigmented and nonpigmented gingiva - Radhika Bharamappa; Vandana Kharidhi Laxman (Wolters Kluwer Medknow Publications, 2013)
Background: It is a known fact that clinical appearance of gingiva directly correlates with the inflammatory status of the periodontium. It has been observed that the gingival thickness (GT) appears to differ in pigmented and nonpigmented gingiva. Thickness of gingiva seems to be of significance and an issue of concern in aesthetic and functional outcome of the periodontal, restorative and orthodontic therapy. So far in the periodontal literature, the gingival width has been discussed to a great extent. GT also plays an equally important role, but it has been given limited importance when compared to gingival width. Purpose of the Study: The purpose of this study was to comparatively assess the GT in pigmented and nonpigmented gingiva by transgingival probing. Materials and Methods: The study included 240 sites in 10 patients each of pigmented and nonpigmented gingiva. The GT was assessed mid-buccally in the attached gingiva, half way between mucogingival junction and free gingival groove and at the base of the interdental papilla. The gingival bleeding index and plaque index were also recorded. The data were statistically analysed using paired t-test and Z-test. Results and Conclusion: Gingival bleeding index and plaque index were similar between both the groups. Both midbuccal and interdental areas were thicker in pigmented gingiva when compared to nonpigmented gingiva.